Antecedents of Corporate Scandals: CEOs’ Personal Traits, Stakeholders’ Cohesion, Managerial Fraud, and Imbalanced Corporate Strategy - Zona, Fabio; Minoja, Mario; Coda, Vittorio (2013)
This study examines the antecedents of corporate scandals. Corporate scandals are defined as rare events occurring at the apex of corporate fame when managerial fraud suddenly emerges in conjunction with a significant gap between perceived corporate success and actual economic conditions. Previous studies on managerial fraud have examined the antecedents of illegal acts in isolation from strategic decisions and in terms of CEOs’ individual responses to the external context. This study frames the antecedents of corporate scandals in terms of the interplay of CEOs’ personal traits with corporate strategy and stakeholders’ cohesion. With this aim, this study builds on extant theory to examine the case of Banca Popolare di Lodi, an Italian bank involved in a corporate scandal in year 2005. The model contributes to advance understanding of the complex dynamics underlying the emergence of corporate scandals.
Keywords: Stakeholders; Managerial fraud; Corporate Strategy; corporate scandals; CEO